PREGNANCY AFTER TREATMENT OF CHORIOCARCINOMA - CASE REPORT - Omer Abuidris, Dafalla; Mohammed, Rehab Sid Ahmed; Mohamed Elgaili, Elgaili; Mohamed Elsanousi, Elsanousi (Gezira Journal of Health Sciences; Vol 4 No 1 (2008), 2008)
Abstract: This is the first case report from its kind to be reported from the Institute of nuclear medicine, Molecular Biology University of Gezira. It is a case report of a 30-years old lady diagnosed as having choriocarcinoma, gestational trophoblastic tumor, and treated with multiple agent chemotherapy for three months. She was advised not to get pregnant during the first two years following chemotherapy. She was on regular follow up for one year after which she disappeared and discontinued the contraceptive pills. Seven months later she presented with a viable pregnancy and was followed till she delivered a normal viable alive boy. Both the lady and her baby are in a good health after six months from delivery.